2023
DOI: 10.1021/acs.jafc.2c07716
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Group of 2,3-Oxidosqualene Cyclase Genes Involved in the Biosynthesis of Diverse Triterpenoids of Perilla frutescens

Abstract: Perilla frutescens (L.), a traditional edible and medicinal crop, contains diverse triterpenes with multiple pharmacological properties. However, the biosynthesis of triterpenes in perilla remains rarely revelation. In this study, nine putative 2,3-oxidosqualene cyclase (OSC) genes (PfOSC1-9) were screened from the P. frutescens genome and functionally characterized by heterologous expression. Camelliol C, a triterpenol with pharmacological effect, was first identified as abundant in perilla seeds, and the cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Finally, the CsOSC1 V484A mutant reduced enzyme activity by 65% and yielded camelliol C (1), a monocyclic triterpene, along with β-amyrin (5) at a ratio of 13:22 (Figures 6A,E, S7 and Table S8). Similar observations were made with the V784A mutant of PfOSC4 and V482A mutant of PfOSC9 from P. frutescens, 41 as well as the V483A/G mutants of EtAS, 44 which predominantly produced camelliol C. The conserved Val residue is known to be vital for B ring formation in triterpene scaffolds through steric hindrance. 45 Its substitution with the smaller Ala or Gly is thought to reduce the bulk size, improperly positioning 2,3-oxidosqualene within the reaction cavity.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Finally, the CsOSC1 V484A mutant reduced enzyme activity by 65% and yielded camelliol C (1), a monocyclic triterpene, along with β-amyrin (5) at a ratio of 13:22 (Figures 6A,E, S7 and Table S8). Similar observations were made with the V784A mutant of PfOSC4 and V482A mutant of PfOSC9 from P. frutescens, 41 as well as the V483A/G mutants of EtAS, 44 which predominantly produced camelliol C. The conserved Val residue is known to be vital for B ring formation in triterpene scaffolds through steric hindrance. 45 Its substitution with the smaller Ala or Gly is thought to reduce the bulk size, improperly positioning 2,3-oxidosqualene within the reaction cavity.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
“… Mutations of the corresponding residues, such as W260L in a multifunctional α-amyrin synthase from C. sasanqua and W257L in a β-amyrin synthase from Perilla frutescens, demonstrated similar effects. , …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…29,30 Shen and co-workers demonstrated that L253 in lupeol synthase PfOSC4 and W257 in β-amyrin synthase PfOSC9 were the critical residues for their product specificity. 35 The F728H mutant of β-amyrin synthase EtAS has been reported to alter its product specificity for producing tricyclic, tetracyclic, and pentacyclic triterpenoids. 18 Recently, the triad motif VFM/N has been found to be the critical determinant for the formation of β-amyrin and cycloartenol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There are a few reports on the altered product specificity of tetracyclic and pentacyclic triterpene synthases. , Shen and co-workers demonstrated that L253 in lupeol synthase PfOSC4 and W257 in β-amyrin synthase PfOSC9 were the critical residues for their product specificity . The F728H mutant of β-amyrin synthase EtAS has been reported to alter its product specificity for producing tricyclic, tetracyclic, and pentacyclic triterpenoids .…”
Section: Resultsmentioning
confidence: 99%